Die Jagd auf den Zins oder: die Fiskalpolitik der Regierung Monti und ihre Folgen - Alexander Grasse (Wirtschaftsdienst, 2012)
Italien leidet politisch und ökonomisch unter der Finanzkrise in der Europäischen Union. Das Wachstum ist negativ und die Arbeitslosigkeit steigt. Obwohl die Neuverschuldung verringert wurde und die Handelsbilanz Überschüsse aufweist, bleibt ein Zinsspread bestehen. Zudem ist zu befürchten, dass die Sparprogramme die Krise weiter verschärfen. Vermögensbezogene Steuern zur Finanzierung von Wachstumsinitiativen wären demgegenüber eine richtige Strategie. – – Mario Monti became Prime Minister of Italy in the autumn of 2011 after the refinancing of Italy's debt in the financial markets had almost failed. The Monti government has since made the lowering of the risk premium for Italy's government bonds an absolute priority. This, however, has only been somewhat successful. Although the new debt was decreased and the balance of trade recorded a surplus, an interest rate spread remains. At the same time, the government's austerity measures only deepened the economic crisis. By contrast, the decision of the ECB in September 2012 to buy government bonds of crisis-ridden states without limitation has proven to be far more effective. The introduction of taxes on higher incomes and wealth to finance growth programmes could now help to resolve the economic crisis.
Keywords: E44; E61; E62; E63; H60; O11; O52; 330; Finanzpolitik; Wirkungsanalyse; Wirtschaftslage; Italien